Customer Service Analysis, Application of Technology Applications, Product Variations on Customer Satisfaction (Study on Livin By Mandiri K CP Jayapura Business Center Products) - Yohanes Ferry Cahaya; Widyarsih AV Rahajeng; Rina Marlina L (Management Research Studies Journal, 2022)
This research was conducted to test whether customer service , product variations , application of technology applications take effect partially and simultaneously on customer satisfaction. The study was conducted at Bank Mandiri KCP Jayapura Sentra Bisnis on Livin by Mandiri products using a sample of 96 people using the SPSS version 27 statistical test tool . Study this test : classical assumption test, namely normality test, heteroscedasticity test, multicollinearity test, multiple regression analysis, hypothesis testing (t test and f test) . The results showed that customer service , application of technology applications, and product variations have a partial and simultaneous impact on customer satisfaction and the application of technology applications is more dominant in influencing customer satisfaction